THE RELATIONSHIP BETWEEN SELF-CONTROL AND NARCISSISTIC TENDENCIES IN STUDENTS USING INSTAGRAM SOCIAL MEDIA - Amanda Octavia; Widyastuti (P3I UMSurabaya, 2024)
The purpose of this study is to determine the relationship between self-control and narcissistic tendencies in students who use Instagram social media. So the hypothesis proposed is that there is a relationship between self-control and narcissistic tendencies in students who use Instagram social media. The population of this study was aimed at students who were studying at the University of Sidoarjo with a sample of 62 students. The data collection method in this study using a self-control scale was revealed using a self-control scale compiled by Lynantawati (2021) and the NPI-16 (Narcissistic Personality Inventory) scale compiled by Ames, Rose, and Anderson and adapted by Nida Monica Ulfa (2022). The data analysis used in the study used Pearson product moment correlation analysis which is used to see the direction and strength of the linear relationship between two variables. The analysis test can be used after the prerequisite test is carried out, the prerequisite tests carried out include normality test and linearity test. This research was assisted by the SPSS version 23.00 for Windows program. Based on data analysis between self-control and narcissistic variables, the correlation coefficient (rxy) value is 0.191 and (p) is 0.137. These results indicate that there is no significant relationship between the self-control variable and the narcissistic tendency variable in students who use Instagram social media. The self-control variable affects the narcissistic variable by 2.1%. and then the remaining 97.9% is influenced by other variables.